Perception of Nigerian journalists in Lagos and Kwara states towards adopting artificial intelligence in journalism practice (Namibian Journal of Linguistics, Literature and Communication Studies, 2025)
The adoption of artificial intelligence (AI) in journalism practice seems to be gaining momentum in many parts of the world including Nigeria. However, the issue of how journalists perceive the adoption of AI and its inherent threats to their profession appears not have been nuanced in the literature, especially in African context. This study, therefore, investigates how journalists in Lagos and Kwara states of Nigeria perceive the adoption of AI in journalism practice as well as its possible threats. The researchers surveyed 376 respondents, selected proportionally among the registered journalists in both states. The study revealed that journalists in Lagos and Kwara states have a positive perception of AI journalism, acknowledging its potential benefits and values, and expressing readiness to adopt the technology. Underpinned with Unified Theory of Acceptance and Use of Technology (UTAUT), the study also found that the adoption of AI was perceived to present certain threats to journalists. These threats include possible job losses, undermining of human creativity and integrity, and the absence of monitoring and control within the industry.
Keywords: Artificial intelligence; journalism; perception; adoption; threat